Calender effect in shariah-compliant stocks returns; Evidence front FTSE Bursa Malaysia hijrah shariah index - Ding, W.H.; Yusof, Z.; Chong, C.S. (2009)
This study aims to investigate the calendar effect in Malaysia Shariah-Cornpliant stocks returns. FTSE Bursa Malaysia Hijrah Shariah (FBMHS) Index is employed. AR(l) in the mean equation and EGARCH (1.1) as variance equation are used to analyze the volatility. Evidence of significant Friday effect, January effect and February effect are found in the FBMHS Index. After conforming the presence of day of the week and month of the year effects, we re-examine one effect by adding another effect in the variance model. We find Friday, January and February effects still exist. However, none of the calendar effects increase or decrease the volatility.